Teachers` gender and primary school pupils` achievement in mathematics in Kenya - Robert, Kati; Owiti, Dickson S.O.; Ongati, Naftali O. (Journal of Education and Practice, 2013)
This descriptive causal comparative study examined the relationship between teacher’s gender and in primary schools pupils’ performance in mathematics in Kenya. The study objective was to investigate the effect of teachers’ gender on primary schools pupils’ mathematics achievement in Vihiga district Kenya. The study was conducted through an ex-post facto research design. A total of 46 mathematics teachers were sampled from 153 schools. Data was collected using a Mathematics Teacher’s Questionnaire (MTQ). Results of a Mathematics Achievement Test (MAT) were used as a measure of teachers’ contribution towards pupils’ academic achievement. Mathematics education experts reviewed the MTQ for content, face and construct validity. A pilot study was also carried out in 2 primary schools outside the district of study. The data collected was translated into frequency counts which were presented in pie and bar charts. Chi square statistic was then used to establish whether there was a relationship between teachers’ gender and its contribution towards pupils’ achievement in mathematics. The findings of the study showed that there was a significant relationship between teachers` gender and pupils` achievement in primary mathematics. The results of this study suggest that more female teachers be trained and deployed to teach mathematics at upper primary school levels since their contribution towards pupils’ performance is profound.
Keywords: teachers` gender; primary school; pupil’s achievement in mathematics